ANALISIS DU PONT DALAM MENGUKUR KINERJA KEUANGAN PT SOLUSI BANGUN INDONESIA TBK - Sihombing, Rossy Pratiwy; Seda Manao, Louis Frans (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to evaluate the financial performance of PT. Solusi Bangun Indonesia Tbk through Du Pont System analysis over a five-year period, from 2021 to 2025. The Du Pont System is applied because it provides integrated financial information by measuring five financial ratios: Net Profit Margin (NPM), Total Asset Turnover (TATO), Return on Investment (ROI), Equity Multiplier (EM), and Return on Equity (ROE). Based on the analysis results, the company performed well from 2021 to 2023, with improvements mainly driven by strong profitability and continuous operational efficiency. However, starting in 2024 and 2025, returns decreased due to a less supportive capital structure; the Equity Multiplier (EM), Net Profit Margin (NPM), and Total Asset Turnover (TATO) all declined. Overall, applying the Du Pont System in this analysis provides a comprehensive explanation of PT. Solusi Bangun Indonesia Tbk's financial performance. This analysis helps identify strengths and areas that need improvement in managing the company's assets and equity, and gives a thorough understanding of how the company can boost its efficiency and profitability in the future.